Enterococcus faecalis strains derived from wild bird provide protection against Clostridium perfringens challenge in locally-sourced broilers - Zhang, Gerui; Zahra, Ainul; Yang, Tianrui; Guo, Qiyu; Sun, Yan; Zhang, Yuhang; Gao, Yupeng; Zhang, Yuxi; Wang, Mingyue; Gong, Jingshuo; Huang, Haibin; Wang, Zhannan; et al. (Frontiers in Veterinary Science, 2025)
IntroductionNecrotic enteritis (NE), caused by Clostridium perfringens, has seen a surge in chicken populations recently due to the ban on antibiotic growth promoters in feed.MethodsIn this research, screening and identification of probiotics with strong antagonistic ability against C. perfringens from 34 wild bird fecal isolates, followed by analysis of probiotic characteristics and carbon source metabolic activity. Strains exhibiting favorable antagonistic activity against C. perfringens were subsequently employed in vivo study to evaluate their protective efficacy against C. perfringens challenge in locally-sourced broilers.ResultsThe results showed that Enterococcus faecalis strains YL-EF25 and YL-EF32 were selected based on their ability to inhibit the growth and biofilm formation of C. perfringens. These two strains demonstrated good tolerance to bile salts, artificial gastric juice, and phenol, as well as metabolic activity toward dietary fiber and propionic acid precursor substances. In vivo tests on locally-sourced broilers revealed that NE induced body weight loss, intestinal lesions, and intestinal inflammation, as well as imbalance in the gut microflora. Administration of E. faecalis YL-EF25 and YL-EF32 can alleviate these symptoms. We find that feed supplementation with YL-EF25 and YL-EF32 reduced the lesion score of challenged chicks (p < 0.05), with increased tight junction-related gene expression (Occludin and ZO-1) and decreased proinflammatory cytokine (TNF-α and IFN-γ) expression in jejunum compared with NE-induced broilers (p < 0.05). Furthermore, E. faecalis YL-EF25 can boost peripheral blood lymphocyte proliferation activity (p < 0.05).DiscussionThese finding indicated that addition of E. faecalis YL-EF25 and YL-EF32 improved growth performance and mitigated NE-induced gut injury, possibly by strengthening intestinal mucosal barrier function and restoring effects on the ileal microbial composition in C. perfringens-challenged broilers.